Mother tongue interference in ESL learning process of students in the Intensive Intermediate English I from the English Teaching Major at the Foreign Language Department of the University of El Salvador, Semester II-2017 - Avalos Benavides, Ivania Lissette; Polanco Navas, Wendy Jasmin (2024)
This research is about Mother Tongue Interference in ESL Learning Process of Students in the Intensive Intermediate English I from the English Teaching Major at the Foreign Language Department of the University of El Salvador, Semester II-2017, the purpose is to help future professionals and to make their acquisition process efficient. In order to justify through theory this study, different researches on language acquisition had been consulted. Thus, in order to determine if there is mother tongue interference the study was carried out focusing on 30 students, as study sample enrolled in the first year of their major currently studying the Intensive Intermediate English I course in the major of English Teaching at the Foreign Language Department of the University of El Salvador. These students were selected randomly at the beginning of the research. Three different quizzes about true and false cognates and English structure were used; data was collected and represented in graphics.